Sonic Hedgehog Signaling in Limb Development - Tickle, Cheryll; Towers, Matthew (Frontiers in Cell and Developmental Biology, 2017)
The gene encoding the secreted protein Sonic hedgehog (Shh) is expressed in the polarizing region (or zone of polarizing activity), a small group of mesenchyme cells at the posterior margin of the vertebrate limb bud. Detailed analyses have revealed that Shh has the properties of the long sought after polarizing region morphogen that specifies positional values across the antero-posterior axis (e.g. thumb to little finger axis) of the limb. Shh has also been shown to control the width of the limb bud by stimulating mesenchyme cell proliferation and by regulating the antero-posterior length of the apical ectodermal ridge, the signalling region required for limb bud outgrowth and the laying down of structures along the proximo-distal axis (e.g. shoulder to digits axis) of the limb. It has been shown that Shh signalling can specify antero-posterior positional values in limb buds in both a concentration- (paracrine) and time-dependent (autocrine) fashion. Currently there are several models for how Shh specifies positional values over time in the limb buds of chick and mouse embryos and how this is integrated with growth. Extensive work has elucidated downstream transcriptional targets of Shh signalling. Nevertheless, it remains unclear how antero-posterior positional values are encoded and then interpreted to give the particular structure appropriate to that position, for example, the type of digit. A distant cis-regulatory enhancer controls limb-bud-specific expression of Shh and the discovery of increasing numbers of interacting transcription factors indicate complex spatiotemporal regulation. Altered Shh signalling is implicated in clinical conditions with congenital limb defects and in the evolution of the morphological diversity of vertebrate limbs.